Reprogramming Neutral Lipid Metabolism in Mouse Dendritic Leucocytes Hosting Live Leishmania amazonensis Amastigotes - Lecoeur, Hervé; Giraud, Emilie; Prévost, Marie-Christine; Milon, Geneviève; Lang, Thierry (PLOS Neglected Tropical Diseases, 2013)
Background After loading with live Leishmania (L) amazonensis amastigotes, mouse myeloid dendritic leucocytes/DLs are known to undergo reprogramming of their immune functions. In the study reported here, we investigated whether the presence of live L. amazonensis amastigotes in mouse bone marrow-derived DLs is able to trigger re-programming of DL lipid, and particularly neutral lipid metabolism. Methodology/Principal Findings Affymetrix-based transcriptional profiles were determined in C57BL/6 and DBA/2 mouse bone marrow-derived DLs that had been sorted from cultures exposed or not to live L. amazonensis amastigotes. This showed that live amastigote-hosting DLs exhibited a coordinated increase in: (i) long-chain fatty acids (LCFA) and cholesterol uptake/transport, (ii) LCFA and cholesterol (re)-esterification to triacyl-sn-glycerol (TAG) and cholesteryl esters (CE), respectively. As these neutral lipids are known to make up the lipid body (LB) core, oleic acid was added to DL cultures and LB accumulation was compared in live amastigote-hosting versus amastigote-free DLs by epi-fluorescence and transmission electron microscopy. This showed that LBs were both significantly larger and more numerous in live amastigote-hosting mouse dendritic leucocytes. Moreover, many of the larger LB showed intimate contact with the membrane of the parasitophorous vacuoles hosting the live L. amazonensis amastigotes. Conclusions/Significance As leucocyte LBs are known to be more than simple neutral lipid repositories, we set about addressing two related questions. Could LBs provide lipids to live amastigotes hosted within the DL parasitophorous vacuole and also deliver? Could LBs impact either directly or indirectly on the persistence of L. amazonensis amastigotes in rodent skin?